Consumer Response to Cause-Related Marketing: A Case of Malaysia - Anuar, Marhana Mohamed; Mohamad, Osman (Journal of Asian Business Strategy, 2012)
Increasing competition in the marketplace makes it difficult to differentiate brand based on the traditional attributes such as price and quality alone. Other attributes of a brand such as ethical and compassionate are becoming more important. “Good” brand or brand that is associated with social or environmental cause is better preferred. Hence, companies are turning to corporate social responsibility (CSR) as a differentiation strategy to gain sustainable competitive advantage. A facet of CSR that is cause-related marketing enables companies to contribute to worthy causes and at the same time fulfilling companies’ objectives. In today’s world there are a multitude of causes exist that need attention and support. In order to enhance the people’s quality of life supporting worthy cause is essential. In light of this, some companies have supported various causes through cause-related marketing (CRM) campaigns. The intention of CRM is to encourage the purchase of a brand or product so that donations can be made to the partnering cause. This study uses a fictitious CRM advertisement to determine the impact of CRM on attitude toward CRM and purchase intention. The study shows that CRM has significant impact on consumers’ attitude as well as purchase intention. Results imply that CRM promises to be an important medium to help worthy causes in Malaysia as consumers in general have positive attitude toward CRM.